Symbolic Interaction of the Meaning of Triwangsa Women's Marriage in Balinese Hindu Culture - Ni Putu Limarandani; Kartika SNLAS; Anak Agung Ketut Patera (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The existence of Hinduism and Balinese culture is an inseparable unity, both of which guide the lives of Balinese people. In Balinese Hindu culture there is a grouping of wangsa as a symbol of identity and social status. Differences in social status will cause differences in behavior in communicating with the audience. The grouping of social status affects the rules of marriage that require women to marry men who have equal social status. Women are not allowed to marry men who have low wangsa because if they do so, the women must go down the wangsa. When a woman has stepped down, there is a change in the way she interacts and communicates with family and society. Changes in the identity of Triwangsa women have a big impact on the doers as well as the family and the environment. This research aims to describe the symbolic interaction in the marriage of Triwangsa women towards the Balinese Hindu family and environment. The results showed that there are differences in interaction patterns between women who descend from the wangsa and women who still have a fixed wangsa.